Can risk factors and risk scores help predict colonization and infection in multidrug-resistant gram-negative bacteria? - Natalia Restrepo-Arbeláez; Juan Carlos García-Betancur; Christian José Pallares; L'Emir Wassim El Ayoubi; Pattarachai Kiratisin; Souha S. Kanj; María Virginia Villegas (Cambridge University Press, 2024)
Antimicrobial resistance (AMR) is positioning as one of the most relevant threats to global public health and threatens the effective treatment of an ever-growing number of bacterial infections in various healthcare settings, particularly in acute care and surgical units, as well as in the community. Among multidrug-resistant (MDR) gram-negative bacteria (MDRGNB), Enterobacterales, Pseudomonas aeruginosa, and Acinetobacter baumannii require special attention, since they account for most of the mortality associated with bacterial infections and are often MDR. It is clear that there is an important global variation in antibiotic resistance profiles among MDRGNB species. Extended-spectrum β-lactamase-producing Enterobacterales, carbapenem-resistant Enterobacterales, DTR-P. aeruginosa, and MDR-A. baumannii are the focus of this review. Here, we summarize a series of relevant studies on risk factors associated with colonization and infection with these MDRGNB. Likewise, we offer a comparative overview of those studies providing scoring systems to predict the risk of infection with these MDR pathogens, and their pros and cons. Despite the variable accuracy of published risk factors for predicting colonization or infection with MDRGNB, these scores are valuable tools that may help anticipate colonization and infection among those colonized. More importantly, they may help reduce unnecessary use of broad-spectrum antimicrobials and guiding the selection of an optimal treatment.